IL‐27 produced during acute malaria infection regulates Plasmodium‐specific memory CD4+ T cells - Maria Lourdes Macalinao; Shin‐Ichi Inoue; Sanjaadorj Tsogtsaikhan; Hirotaka Matsumoto; Ganchimeg Bayarsaikhan; Jiun‐Yu Jian; Kazumi Kimura; Yoshiaki Yasumizu; Tsuyoshi Inoue; Hiroki Yoshida; Julius Hafalla; Daisuke Kimura; et al. (EMBO Molecular Medicine)
Abstract Malaria infection elicits both protective and pathogenic immune responses, and IL‐27 is a critical cytokine that regulate effector responses during infection. Here, we identified a critical window of CD4+ T cell responses that is targeted by IL‐27. Neutralization of IL‐27 during acute infection with Plasmodium chabaudi expanded specific CD4+ T cells, which were maintained at high levels thereafter. In the chronic phase, Plasmodium‐specific CD4+ T cells in IL‐27‐neutralized mice consisted mainly of CD127+KLRG1− and CD127−KLRG1+ subpopulations that displayed distinct cytokine production, proliferative capacity, and are maintained in a manner independent of active infection. Single‐cell RNA‐seq analysis revealed that these CD4+ T cell subsets formed independent clusters that express unique Th1‐type genes. These IL‐27‐neutralized mice exhibited enhanced cellular and humoral immune responses and protection. These findings demonstrate that IL‐27, which is produced during the acute phase of malaria infection, inhibits the development of unique Th1 memory precursor CD4+ T cells, suggesting potential implications for the development of vaccines and other strategic interventions.